Convergence of the National Accounting System with Ifrs: Problems and Prospects - Professor G.S. Jambakieva (Periodica Journal, 2022)
The article is devoted to the issues of the need for convergence of national accounting based on the achievements of European practice, in particular International Financial Reporting Standards (IFRS). The necessity and main directions of accounting reform are described. The problems of using IFRS in practice in the accounting of companies and, as a result, maintaining parallel accounting according to national accounting standards and international financial reporting standards are outlined. This article discusses the international convergence of accounting standards, the stages of its development, the need to analyze international experience. For Uzbekistan, this is a necessary study, since we are in the period of accession to the World Trade Organization (WTO). We need to take into account all the nuances of joining the WTO, eliminate some shortcomings and apply recommendations for the organization of national accounting.
Keywords: Accounting; AccountingNSB; IFRS; parallel accounting.